The Relationship between Motivation to Learn Biology and Discipline with Students’ Cognitive Learning Outcomes during Online Learning - Heryanti, Erna; Azrai, Eka Putri; Melvinasari, Mega Widia (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2022)
Biology learning and teaching process become more challenging during the Covid-19 pandemic since it is done online. The learning outcomes of the biology lesson during online learning are important for students’ academic achievement. Motivation to learn biology and discipline of students are factors that can influence students’ learning outcomes during online learning. This study aims to determine the correlation between motivation to learn biology and discipline with students’ cognitive learning outcomes during online learning. The research was conducted in February to June 2021 using a descriptive quantitative method with correlational study technique. The sample used was 179 students of grade X MIPA who were selected through simple random sampling technique. The data was collected by survey technique using motivation to learn biology questionnaire, discipline in learning biology during online learning questionnaire, and multiple-choice tests of cognitive learning outcomes. The research results showed that there is a positive correlation between motivation to learn biology with students’ cognitive learning outcomes, a positive correlation between discipline in learning biology during online learning with students’ cognitive learning outcomes, and a positive correlation between motivation to learn biology and discipline in learning biology during online learning with students’ cognitive learning outcomes.